PENGARUH PENGGUNAAN DOMPET ELEKTRONIK (E-WALLET) SHOPEEPAY TERHADAP PERILAKU KONSUMTIF MAHASISWA DI KOTA MALANG (STUDI KASUS PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS BRAWIJAYA) - Nurman Setiawan Fadjar; Lidya Virginia (Journal of Development Economic and Social Studies, 2024)
The increasingly advanced development of information technology provides new things in the economic sector in keeping up with increasingly modern development. One of them is the emergence of  ShopeePay. ShopeePay is a digital wallet service issued by Shopee and currently very popular with the public because it provides convenience and benefits in terms of trasactions. This study aims to determine the effect of using ShopeePay electronic e-wallet on the consumptive behaviour of student in the city of Malang by tooking at the perceived of ease, perceived of use, and promotion as indicators in this study. The method used is SmartPLS (Partial Least Square). The result showed that perceived of ease, perceived of use, and promotion had a positive and significant effect on the comsumptive behaviour of students in the cinty of Malang.